2019
DOI: 10.1093/ckj/sfz097
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory leucocyte infiltrates are associated with recovery in biopsy-proven acute interstitial nephritis: a 20-year registry-based case series

Abstract: Background Acute interstitial nephritis (AIN) is a renal injury causing renal function deterioration and requiring renal replacement therapy (RRT) in a substantial number of cases. Therapy is based on withdrawal of suspicious causative drugs or the underlying diseases and/or steroid application if renal function is not restored after cessation of the underlying condition. Hard clinical evidence for augmenting steroid therapy is not available. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…We also found that higher interstitial infiltrate was associated with better kidney function. Such association of interstitial infiltrate with higher eGFR on follow-up was also noted in the Boston Kidney Biopsy Cohort, which included a broad group of kidney pathology diagnoses [36] and in a recent study of 49 patients with AIN [37]. Presence of interstitial infiltrate is a potentially treatable pathology; it could represent responsiveness to immunosuppressive therapy and thus be associated with higher kidney function.…”
Section: Discussionmentioning
confidence: 56%
“…We also found that higher interstitial infiltrate was associated with better kidney function. Such association of interstitial infiltrate with higher eGFR on follow-up was also noted in the Boston Kidney Biopsy Cohort, which included a broad group of kidney pathology diagnoses [36] and in a recent study of 49 patients with AIN [37]. Presence of interstitial infiltrate is a potentially treatable pathology; it could represent responsiveness to immunosuppressive therapy and thus be associated with higher kidney function.…”
Section: Discussionmentioning
confidence: 56%
“…In fact, patients with AIN lost a median of 11 ml/min per 1.73 m 2 of eGFR from baseline to 6 months after biopsy (94). Greater interstitial fibrosis is associated with lower kidney function recovery, whereas greater interstitial inflammation is associated with improved kidney function recovery and more dialysis discontinuation (83,94,95). Corticosteroids were most beneficial in patients with greater interstitial infiltrate, higher eGFR before biopsy, and higher urine IL-9 levels (83,94).…”
Section: Treatmentmentioning
confidence: 99%
“…AIN is an uncommon cause of AKI in the pediatric population, accounting for 0.87%∼15.7% of AKI in all children [ 1–2 ], and 27% in adults. AIN is usually caused by drugs, while other causes include autoimmune diseases [ 3 ] (systemic lupus erythematosus, Sjogren’s syndrome, sarcoidosis, IgG4-related immunoglobulin diseases), infections [ 4 ] (Legionella, Leptospira, Streptococcus, Corynebacterium, mycoplasma, hantavirus, measles, Epstein Barr virus, cytomegalovirus, HIV, etc. ), herbal remedies and neoplastic conditions, etc.…”
Section: Introductionmentioning
confidence: 99%